The organization of African unity - Addona, A. F. (Cleveland, World Pub. Co., 1969)
A history of the development of African countries, their struggle for independence, and the creation of The Organization of African Unity which aids members in achieving their common goals by rendering technical, administrative, and economic assistance.
Bibliography: p. 216-218.
Keywords: Organization of African Unity -- Juvenile literature; Organization of African Unity; Africa; Politics and government; Africa -- Politics and government -- Juvenile literature; Africa -- Politics and government